Chlamydia trachomatis TmeB antagonizes actin polymerization via direct interference with Arp2/3 activity - Scanlon, Kaylyn R.; Keb, Gabrielle; Wolf, Katerina; Jewett, Travis J.; Fields, Kenneth A. (Frontiers in Cellular and Infection Microbiology, 2023)
Chlamydia trachomatis is an obligate intracellular pathogen that actively promotes invasion of epithelial cells. A virulence-associated type III secretion system contributes to chlamydial entry and at least four effectors have been described that are deployed during this time. Two of these invasion-related effectors, the translocated membrane-associated effectors A and B (TmeA and TmeB), are encoded in a bi-cistronic operon. TmeA directly activates host N-WASP to stimulate Arp2/3-dependent actin polymerization. According to current working models, TmeA-mediated N-WASP activation contributes to invasion. TmeB has not been functionally characterized. Unlike a tmeA null strain, loss of tmeB does not impact invasion efficiency of C. trachomatis. Using strains deficient for multiple genes, we provide evidence that TmeA is dispensable for invasion in the absence of TmeB. Our data indicate that overabundance of TmeB interferes with invasion and that this activity requires active Arp2/3 complex. We further show that TmeB is capable of interfering with Arp2/3-mediated actin polymerization. In aggregate, these data point to opposing functions for TmeA and TmeB that manifest during the invasion process. These studies raise intriguing questions regarding the dynamic interplay between TmeA, TmeB, and branched actin polymerization during chlamydial entry.